2023
DOI: 10.1155/2023/3538928
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognostic Biomarker KIAA1522 Is Associated with Immune Infiltrates in Hepatocellular Carcinoma

Abstract: Background. The prognosis is poor for hepatocellular carcinoma (HCC), a tumor and cancer associated with inflammation that is common. New data showed that significant levels of KIAA1522 were expressed in HCC tissues and cell lines, suggesting that KIAA1522 may be a highly useful prognostic marker for HCC. However, its biochemical processes and impacts on the immune system go deeper. Objective. To verify the significance of KIAA1522 in HCC and investigate its related carcinogenic mechanisms. Methods. Studies ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Low expression of ALDH7A1 protein is related to poor prognosis in HCC patients 88 . KIAA1522 expression in HCC tumour tissue is elevated and indicates poor prognosis, possibly due to inhibition of PPAR signalling pathways 89 . Through data‐independent acquisition, quantitative proteomics, bioinformatics methods and experimental validation, Zhang et al 90 .…”
Section: Ppars and Related Pathways As Prognostic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Low expression of ALDH7A1 protein is related to poor prognosis in HCC patients 88 . KIAA1522 expression in HCC tumour tissue is elevated and indicates poor prognosis, possibly due to inhibition of PPAR signalling pathways 89 . Through data‐independent acquisition, quantitative proteomics, bioinformatics methods and experimental validation, Zhang et al 90 .…”
Section: Ppars and Related Pathways As Prognostic Biomarkersmentioning
confidence: 99%
“… 88 KIAA1522 expression in HCC tumour tissue is elevated and indicates poor prognosis, possibly due to inhibition of PPAR signalling pathways. 89 Through data‐independent acquisition, quantitative proteomics, bioinformatics methods and experimental validation, Zhang et al. 90 revealed that the low expression of acyl‐CoA oxidase 2 (ACOX2) in HCC indicated an unfavourable prognosis.…”
Section: Ppars and Related Pathways As Prognostic Biomarkersmentioning
confidence: 99%
“…A Wilcoxon test was used to examine the correlation between immune clusters and immune checkpoints (ICPs) and SLC8A1. With the ggplot2 R package, immunological correlation scores and immune checkpoint analyses were plotted [25].…”
Section: Correlation Analysis Between Slc8a1 and Immune Checkpointmentioning
confidence: 99%